(untitled) (Asian Journal of Medical and Biological Research, 2015)
This study was aimed to determine the seroprevalence of foot and mouth disease (FMD) in cattle and identifying the potential risk factors associated with the disease among sedentary cattle in northern part of Plateau state, Nigeria. Two hundred and seventy cattle aged from 6 months to ?3 years old were randomly selected and identified and whole blood collected from the jugular vein using plain evacuated tubes. Whole blood was processed and separated and sera were screened for foot and mouth disease virus (FMDV) 3D non-structural proteins using blocking enzyme linked immunosorbent assay (ELISA). Overall, 55.9% (95%CI: 49.96-61.77) FMD seroprevalence was obtained from the study area. Seroprevalence was highest in Riyom (82.5%), followed by Barkin Ladi (66.2%), Jos South (55.5%) and Bassa (41.2%) (x2 = 17.21, P<0.05). Risk factors for age, management system and location were significant associated (P<0.05) with seroprevalence of FMD. However, there was no significant association with sex (P>0.05). The prevalence odd ratio of FMD was more in Riyom than in Jos South, Barkin Ladi and Bassa (P<0.05). Prevalence odd ratio of FMD was more in extensively managed system relative to intensively managed system, more in adult cattle aged >2 years old. This study has indicated that FMD is an important disease among sedentary cattle in Northern Plateau, however little is currently known about the economic impact of the disease on the local farmers and their livelihoods. As a control measure, efforts should be improved on animal movement during outbreaks while prophylactic control using vaccination should be considered as another option using vaccines containing virus representative of the region. Asian J. Med. Biol. Res. June 2015, 1(2): 169-174